Is Cloud Secure? - Balamurugan, B; Marimuthu, K; Rajkumar, S; Alenezi, Mamdouh; Niranchana, R (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is the buzz word, the corporate world pronounces every now and then. All the software companies are looking for a where about to store their data at a low cost and reduce the problem of selecting and updating a suitable infrastructure. The mushroom growth of startups and their prosperity and share in the software trends has also mounted the need of cloud computing. On the other hand, several other problems have taken birth like the believability of the cloud and the security concerns of it [1].The cloud users are stranded in a situation either to believe cloud or to wait for some more time for transiting to cloud .This position paper gives a thorough analysis of the cloud security and the stand the cloud computing has taken currently.